The new chemistry - Hall, Nina. ([S.l.] : Cambridge University Press, 2000)
This original and fascinating book highlights the most important developments in chemistry over the past thirty years. The New Chemistry covers the latest research trends in a wide range of fields, both theoretical and experimental. It consists of seventeen self-contained chapters, each covering a different topic in chemistry, ranging from the discovery of new elements and synthetic techniques to the design of drugs and materials. Each chapter is written by one of the world's leading chemists in that particular field, including several Nobel Prize winners. Throughout, the volume is copiously illustrated with photographs and explanatory diagrams. Written in a lively and accessible style, this showcase for modern chemistry will interest all readers and also serve as a useful reference.
Keywords: chemistry